Validity of the Brief Assessment of Impaired Cognition case‐finding instrument for identification of dementia subgroups and staging of dementia. (5th December 2022) - Jørgensen, Kasper; Nielsen, Thomas Rune; Nielsen, Ann; Waldorff, Frans Boch; Høgh, Peter; Gottrup, Hanne; Vestergaard, Karsten; Oxbøll, Anne‐Britt; Waldemar, Gunhild
Abstract: Background and purpose: The aims of this study were to examine the psychometric properties of the Brief Assessment of Impaired Cognition (BASIC) case‐finding instrument in clinical settings focusing on (i) test–retest reliability, (ii) the discriminative validity of BASIC and its components for identification of Alzheimer disease (AD) dementia and non‐AD dementia, and (iii) the association of expert clinical rating of cognitive status with BASIC performance. Methods: The test–retest reliability analysis was based on a sample of general practice patients ( n  = 59) retested with a mean interval of 19 days. Discriminative validity analyses and analysis of the association of cognitive status with BASIC performance were based on data from the primary validation study of BASIC in memory clinics. Results: The test–retest reliability of BASIC was high ( r  = 0.861). No significant difference in discriminative validity was found for identification of AD dementia (sensitivity = 0.99, specificity = 0.98) and non‐AD dementia (sensitivity = 0.90, specificity = 0.98). All components of BASIC contributed to the high discriminative validity of both AD and non‐AD dementia. BASIC performance was significantly correlated with expert clinical rating of the cognitive status of patients. A crude staging model for cognitive status using BASIC score intervals had superior classification accuracy (70%) compared to a Mini‐Mental State Examination (MMSE) score range‐based model (58% accuracy). Conclusions: BASIC is a reliable and valid case‐finding instrument for AD dementia and non‐AD dementia in clinical settings. BASIC performance is significantly associated with the degree of cognitive impairment, and BASIC seems to be superior to MMSE for staging of impairment. Abstract : Accurate and quick case‐finding instruments for identification of patients with possible dementia in general practice and other clinical settings are needed. The Brief Assessment of Impaired Cognition (BASIC) has high test–retest reliability and high discriminative validity for identification of both Alzheimer and non‐Alzheimer dementias. BASIC performance is significantly correlated with expert clinical rating of the cognitive status of patients, and a crude staging model for cognitive status using BASIC score intervals is superior to a Mini‐Mental State Examination score interval‐based staging model.